The creativity of islamic education teachers in fostering interest in learning islamic education at sd negeri 104 oku - Aris Eko Cahyono; Monika Putri; Marliat Marliat (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Teacher creativity in the learning process is a crucial aspect in creating a fun learning environment and motivating students to actively participate in learning activities, particularly in Islamic Religious Education (PAI). This study aims to describe the forms of PAI teacher creativity and their impact on student learning interest at SD Negeri 104 OKU. This research used a descriptive qualitative approach, with data collection techniques including in-depth interviews, participant observation, and documentation. The results indicate that PAI teacher creativity manifests itself in three main ways: a variety of learning methods (discussions, demonstrations, and question-and-answer sessions), the use of learning media (visual and audiovisual), and teacher role models in religious and communicative behavior. These three aspects have been proven to increase student learning interest, as evidenced by increased student participation, enthusiasm, and responsibility in learning. Thus, PAI teacher creativity is a strategic factor in creating a learning climate that supports the strengthening of religious values and character in students from an early age.